A design-of-experiments approach to estimate the effect of plasma-treatment parameters on the mechanical resistance of adhesive-bonded joints. (July 2021) - Mandolfino, Chiara; Cassettari, Lucia; Pizzorni, Marco; Saccaro, Stefano; Lertora, Enrico
Abstract: In this study, the design of experiments (DoE) approach was used to identify the effect of low-pressure plasma surface treatment parameters on the lap-shear strength of adhesive bonded joints realized using different substrates. In particular, four different polymeric substrates were considered: 5- and 7-layer carbon-fiber reinforced polymers and polyamide 6 and 6.6. Two-level, full-factorial designs were used to investigate the effects of two varying principal parameters, namely, plasma power and treatment time, for each type of substrate. The analysis was carried out by considering different types of processing gases. The objective function was the tensile shear strength of the adhesively bonded joints. For each set of joints, the shear strength values​​ ​​were compared using the DoE approach to detect any systematic behavior among different substrates. Finally, it was possible to identify the set-up parameters that gave the best performance in terms of shear strength, considering any equivalent conditions from a statistical point of view. This aspect is particularly important in consideration of the process optimization of the manufacturing cycle; indeed, it allows the maximization of the joint efficiency by limiting the energy cost for treatment.